Using the Non- Homogenous Poisson Processes with Queuing Theory in the Emergency Department in Al-Tifel Teaching Central Hospital (Al-Iskan) - عباس الطائي خالد ضاري; محمد حسين زينة معين (Journal of Economics and Administrative Sciences, 2011)
In this paper, the using of Non-Homogenous Poisson Processes, with one of the scientific and practical means in the Operations Research had been carried out, which is the Queuing Theory, as those operations are affected by time in their conduct by one function which has a cyclic behavior, called the (Sinusoidal Function). (Mt / M / S) The model was chosen, and it is Single Queue Length with multiple service Channels, and using the estimating scales (QLs, HOL, HOLr) was carried out in considering the delay occurring to the customer before his entrance to the service, with the comparison of the best of them in the cases of the overload. Through the experiments of simulation, (QLs) scale was the best scale in considering the least delay for the customer, and also to reach the best experiment (B) in order to reduce the delay occurring to the customer before his entrance to the service in the cases of the over load. That was applied to the application.